(3GdMSjfjI aj GdBOGHs - (3GdCfWGcj, MSjf Hf YHO Gddg, (B1130 (3g`s ((3LGeY GdYKeGfjI (B- (3MdHs)
(3ChdgG (B:s
(3jG ef habfG dhXGFa GdHMK aj GdJMQjQGJ hGdJMbjbGJ (B... (3agPg YLGdI cGajI dhSGFd GdSGFdjf dhXGFa GdcdGe hZdGdI TGajI dYdd GdeYddjf Ydi MI GdebGd hGdeQGe hLGeYI ddaQGFO GdefXheI s
(3BNQgG (B:s
... (3agj cGdChd aj LejY GdCMhGd eY GdefY GdeLGj GddZhj hGdeYGQVI GdJbOjQjI HdG GMJjGL Edi GYJHGQ GdOYhi hdYd GdUhGH GdSGHb dHYV GdaVdGA hLGR fajgG dcf HdG GSJKHfGA JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\617s
(3EjVGM Gdecfhf (B1\406s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs